Eco-friendly four spectrophotometric approaches for the simultaneous determination of the recently FDA-approved combination, bupivacaine and meloxicam in pharmaceutical dosage forms - Aya Saad Radwan; Mohamed M. Salim; Fathalla Belal; Galal Magdy (Scientific Reports, 2024)
Abstract In this study, bupivacaine (BUP) and meloxicam (MLX) were simultaneously assayed in their co-formulated ampoules without interference using four affordable, sensitive, and eco-friendly spectrophotometric methods. The assay of MLX at 359.3 nm over the concentration range of 1.0–15.0 µg/mL was accomplished using a direct UV-spectrophotometric method (Method I) without interference from BUP. However, there was a significant overlap between the spectra of BUP and MLX, making it difficult to determine BUP directly from the UV spectrum. Therefore, various UV-based techniques, including second derivative spectrophotometry (Method II), ratio subtraction method (Method III), and absorption factor method (Method IV), were used to determine BUP over the concentration range of 5.0–80.0 µg/mL. The proposed methods could simultaneously determine the studied drugs with a challenging ratio of 33.3:1.0 (BUP: MLX), which increases the importance of the current study. The proposed methods were applied to estimate the studied drugs in commercial ampoules with high % recoveries and low %RSD values. The excellent eco-friendliness of the developed methods was demonstrated using GAPI and AGREE metrics. The developed methods were validated according to ICHQ2(R2) guidelines. The proposed methods can be better suited for the routine analysis of BUP and MLX in their fixed-dose combination with high selectivity.